2019
DOI: 10.1111/1756-185x.13671
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and risk factors for pulmonary arterial hypertension associated with primary Sjögren’s syndrome: 15 new cases from a single center

Abstract: Aim This study aimed to retrospectively describe 15 new primary Sjögren's syndrome‐pulmonary arterial hypertension (pSS‐PAH) cases confirmed by right heart catheterization (RHC). Demographic and clinical characteristics were analyzed and risk factors for PAH in pSS were explored. Method We retrospectively described 15 new pSS‐PAH cases confirmed by RHC referred to our institution between January 2013 and March 2018. We present PAH and pSS characteristics, hemodynamic evaluations, medical management, and outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…CTD-PAH individuals also had signi cantly higher RV and RA values than CTD-non-PAH patients, and they were more likely to develop secondary pericardial effusions (P < 0.001). Furthermore, we found that pericardial effusion was a risk factor for CTD-PAH, and there have been similar reports in the past [38][39][40].…”
Section: Discussionsupporting
confidence: 87%
“…CTD-PAH individuals also had signi cantly higher RV and RA values than CTD-non-PAH patients, and they were more likely to develop secondary pericardial effusions (P < 0.001). Furthermore, we found that pericardial effusion was a risk factor for CTD-PAH, and there have been similar reports in the past [38][39][40].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, in the present study, 17 of 46 patients (37.0%) had pericardial effusion by echocardiography. The literature suggests that pericardial effusion relates to RV failure and immunologically mediated inflammatory conditions [ 15 ]. Pericardial effusion is an increasingly recognized risk factor of PAH related to CTD [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a prospective cohort study of SS-associated PAH in China suggested that PAH screening should be conducted for SS patients with pericardial effusion, liver involvement, Raynaud’s phenomenon, and high-titer rheumatoid factor. [ 24 , 32 ] If the screening does not indicate PAH but the primary disease activity persists in a high level or deteriorates, the screening should be repeated within 3–6 months. If the screening does not indicate PAH and the disease activity remains at a low level or the patient does not show new symptoms, the screening should be repeated once a year.…”
Section: Introductionmentioning
confidence: 99%